Nifedipine and diltiazem reduce pulmonary edema formation during postischemic reperfusion of the rabbit lung - Karck, Matthias; Haverich, Axel (Research in experimental medicine, 1992)
A protective effect of calcium antagonists in pulmonary preservation for transplantation has been observed recently. This report focuses on the potential use of diltiazem and nifedipine in the early phase of reperfusion after normothermic pulmonary ischemia. Rabbits weighing 4-5 kg were tracheotomized and ventilated with 50% oxygen. In a control group (group I,n=7), the hilus of the right lung was clamped for 210 min without ischemia of the left lung. Lung ischemia was created in a second group (n=7) by clamping the left hilum for 2 h. Subsequently, reperfusion of the left lung was maintained for 210 min, while the right hilus was kept occluded. In group III (n=6) and group IV (n=8) the conditions were the same as in group II, but either diltiazem (62.5 μg/kg i.v., group III) or nifedipine (3 μg/kg i.v., group IV) was administered during the first 20 min of reperfusion. After 210 min of reperfusion, the pulmunary vascular resistance was elevated in group II (×: 5120 dyn·sec·cm−5), group III (5518 dyn·sec·cm−5), and group IV (4324 dyn·sec·cm−5), compared with group I (3390; n.s.). Arterial oxygenation showed no significant differences among group I (×: 257 mmHg), group II (261 mmHg), group III (208 mmHg), and group IV (247 mmHg). Pulmonary ischemia resulted in an increased extravascular lung water content in group II as compared to group I (73 and 64 g/g wet weight;P<0.0125 vs group I). No such increase was seen in groups III and IV (53 and 54 g/g wet weight respectively;P<0.001 vs group II). In this model of normothermic left lung ischemia, the application of diltiazem or nifedipine during the early phase of reperfusion limits formation of pulmonary edema. In constrast to previous findings using verapamil, both substances do not show significant influence on pulmonary vascular resistance. They may be of use in clinical lung transplantation by reducing fluid accumulation in the lung parenchyma.